Pengaruh Program Makan Bergizi Gratis (MBG) terhadap Pendapatan Pedagang Pasar Panorama Kota Bengkulu - Shinta Wiji Rahayu; Yohanes Susanto (Jurnal Adminitrasi Bisnis Nusantara, 2026)
This study aims to analyze the effect of the Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) on traders’ income at Panorama Market, Bengkulu City. The MBG program is a government policy that not only focuses on improving students’ nutritional status but also has the potential to generate economic impacts through increased demand for local food commodities. This research uses a quantitative approach with a descriptive method. The sample consists of 50 food traders selected using purposive sampling. Data were analyzed using simple linear regression, t-test, and coefficient of determination (R²). The results show that the MBG program has a positive and significant effect on traders’ income. This is evidenced by the regression equation Y = 2.03 + 2.12X, a t-value of 4.71 which is greater than the t-table value of 2.01, and an R² value of 0.75, indicating that 75% of the variation in traders’ income is explained by the MBG program. The most significant impact is experienced by traders of essential food commodities such as vegetables, eggs, and meat. In conclusion, the MBG program not only contributes to social welfare through improved nutrition but also acts as a driver of local economic activity by increasing trade activities in traditional markets, Bengkulu City.